Prosthetic management of unfavourable nasal defect: a case report / Sayfaldeen Kashmoola and Tengku Fazrina Tengku Mohd Ariff - Kashmoola, Sayfaldeen; Tengku Mohd Ariff, Tengku Fazrina (Faculty of Dentistry, Universiti Teknologi MARA, 2021)
Facial defects can affect the appearance of an individual, resulting in psychological and social problems. In certain cases, surgical reconstruction of facial defects may not be feasible and prosthodontic rehabilitation may be the best option. Case description: A 72-years old gentleman was referred for the rehabilitation of a facial defect on the right side of his nose. The defect was affecting him psychologically and socially. The decision was made to construct a nasal prosthesis for him that would be retained by desirable undercuts and adhesive. Management of facial defects are challenging due to multiple reasons such as matching of the prosthesis to surrounding skin and retention of the prosthesis. The prosthesis can be retained with implants, facial accessories, desirable undercuts, or adhesives. For this patient, the prosthesis was retained by using undercuts combined with medical-grade adhesive. A thin layer of flash at the edges of the prosthesis was maintained to ensure even finish margin. The prosthesis fabrication successfully resolved the patient’s condition.